Women of War: the Italian Assassins, Spies, and Couriers Who Fought the Nazis - Cope, Suzanne, 1978- ([New York, New York] : Dutton, 2025)
"From underground soldiers to intrepid spies, Women of War unearths the hidden history of the brave women who risked their lives to overthrow the Nazi occupation and liberate Italy. Using primary sources and brand new scholarship, historian Suzanne Cope illuminates the roles played by women while Italians struggled under dual foes: Nazi invaders and Italian fascist loyalists. Cope's research and storytelling introduces four brave and resourceful women who risked everything to overthrow the Nazi occupation and pry their future from the fascist grasp. We meet Carla Capponi in Rome, where she made bombs in an underground bunker then ferried them to their deadly destination wearing lipstick and a trenchcoat; and Bianca Guidetti Serra who rode her bicycle up switchbacks in the Alps, dodging bullets while delivering bags of clandestine newspapers and munitions to the anti-fascist armies hidden in the mountains. In Florence, the young future author of Italy's new constitution, Teresa Mattei, carried secret messages and hid bombs; while Anita Malavasi led troops across the Apennine Mountains. Women of War brings their experiences as underground resistance fighters, partisan combatants, spies, and saboteurs to life. Essential and original, Women of War offers not only a reexamination of the elision of women from vital WWII history but also a valuable perspective on the ongoing fight for gender equality and social justice. After all, these were the women who launched a feminist movement as they fought for the future of their country, and what that could mean for its women, all while under Nazi and fascist fire"--
War Comes to Italy -- Resistance -- Liberation.
Includes bibliographical references and index.
Keywords: Malavasi, Anita, -- 1921-2011.; Guidetti Serra, Bianca; Mattei, Teresa, -- 1921-2013.; Capponi, Carla, -- 1918-2000.; World War, 1939-1945 -- Underground movements -- Italy; Women guerrillas -- Italy -- Biography; Female assassins -- Italy -- Biography; Women spies -- Italy -- Biography; Guerrillas -- Italy -- Biography; Assassins -- Italy -- Biography; Spies -- Italy -- Biography